Aktivis Feminis Akademik: Pengetahuan Perempuan untuk Resistensi, Harapan, dan Perubahan Sosial. Kontribusi Jurnal Perempuan dalam Membangun Diskursus Feminisme di Indonesia - Retno Daru Dewi G. S. Putri; Abby Gina Boang Manalu; Nur Iman Subono (Jurnal Perempuan, 2022)
From 1996 to 2021, Jurnal Perempuan has been disseminating feminist knowledge for 25 years. A total of 610 scientific papers have been published in 110 editions under 11 different main topics. In addition to feminist literature, which is published three times a year, Jurnal Perempuan’s research results also underlie a number of movements and advocacy in fighting for feminism and gender issues. The transformation of feminist theories into real practice is manifested in public discussions, collective actions, video documentaries, to the participation of Sahabat Jurnal Perempuan. This qualitative research aims to reflect on the publication of Jurnal Perempuan over the last 25 years and how Jurnal Perempuan turns academic research into activism against oppression and violence. Using the ethnography or autoethnography method, this paper will describe how Jurnal Perempuan implements feminist praxis in building a feminist discourse through feminist literature, education, advocacy, and solidarity.